The mental corpus ; how language is represented in the mind - Taylor, John R., 1944- (Oxford : Oxford University Press, 2012)
John Taylor argues that an individual's knowledge of a language is a repository of memories. Similarities between items lead to generalisations then used to generate new expressions. He makes a compelling contribution to understanding language and the operations of the mind.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Neurolinguistics; Psycholinguistics; Language and languages -- Physiological aspects; Language awareness; Language acquisition -- Physiological aspects